Eating Behaviors Related to Anemia Prevention in Young Women in Jayapura City - Bela, Sarni Ranteallo; Rumaropen, Nova Falentina (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Based on previous interviews with health workers at the City Health Office, health services for adolescent girls were carried out by the school by activating the UKS (School Health Business) assisted by the puskesmas, and cadres, but with the closure of schools during the coronavirus pandemic, so health services were limited and This is not optimal and this can have an impact on health, especially young women in receiving services such as giving Fe tablets, monitoring nutritional status and education about health problems for young women. The risk of anemia can be experienced in young women who are vulnerable if they are not supervised in terms of health services and eating behavior of young women.This type of research is descriptive using a cross-sectional study design. The aim of the study was to obtain an overview of the eating behavior of adolescent girls in Jayapura City. The research will be conducted in the work area of the Jayapura City Health Office. Research time for 8 months. The sample is 100 respondents from a population of 26,084 young women. The eating behavior interview of adolescent girls was conducted by assessing the level of knowledge, attitudes and actions. Data analysis was carried out in this study using a computer software system, namely SPSS 16. Statistical test to see the frequency distribution of eating behavior of adolescent girls. The results of the study showed that most of the young women had good knowledge as many as 62 respondents (82.7%), the attitude towards preventing anemia was mostly good, namely 51 (68.0%) but most of the young women had inadequate actions in preventing anemia, namely 69 (92.0%).